Clinical and Economic Benefit of Achieving Disease Control in Psoriatic Arthritis and Ankylosing Spondylitis: A Retrospective Analysis from the OM1 Registry - Bergman, Martin J.; Zueger, Patrick; Patel, Jayeshkumar; Saffore, Christopher D.; Topuria, Ia; Cavanaugh, Cristi; Fang, Siran; Clewell, Jerry; Ogdie, Alexis (Rheumatology and therapy., 2023)
Background There is limited evidence on the clinical and economic benefit of achieving disease control in psoriatic arthritis (PsA) and ankylosing spondylitis (AS), thus we aimed to assess the impact of disease control on healthcare resource use (HCRU) and direct medical costs among US patients with PsA or AS over 1 year. Methods Data were derived from the US OM1 PsA/AS registries (PsA: 1/2013–12/2020; AS: 01/2013–4/2021) and the Optum Insight Clinformatics® Data Mart to identify adult patients with PsA or AS. Two cohorts were created: with disease control and without disease control. Disease control was defined as modified Disease Activity Index for Psoriatic Arthritis (DAPSA28) ≤ 4 for PsA and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) < 4 for AS. Outcomes were all-cause inpatient, outpatient, and emergency department (ED) visits and associated costs over a 1-year follow-up period. Mean costs per person per year (PPPY) were assessed descriptively and adjusted odds ratios (aOR) with 95% confidence intervals (CI) were estimated for the likelihood of HCRU by logistic regression. Results The study included 1235 PsA (with disease control: N = 217; without: N = 1018) and 581 AS patients (with disease control: N = 342; without: N = 239). Patients without disease control were more likely to have an inpatient (aOR [95% CI]; PsA: 3.0 [0.9, 10.1]; AS: 7.7 [2.3, 25.1]) or ED (PsA: 1.6 [0.6, 4.2]; AS: 3.5 [1.5, 8.3]) visit than those with disease control. Those without disease control, vs. those with disease control, had greater PPPY costs associated with inpatient (PsA: $1550 vs. $443), outpatient (PsA: $1789 vs. $1327; AS: $2498 vs. $2023), and ED (PsA: $114 vs. $57; AS: $316 vs. $50) visits. Conclusions Findings from this study demonstrate lower disease activity among patients with PsA and AS is associated with less HCRU and lower costs over the following year.